Digestibility of protein sources in feed for Oreochromis aureus x O. nilotica - Degani, Gad; Yehuda, Yehuda (Indian Journal of Fisheries, 2011)
The digestibility of various diet components (sunflower seed, rapeseed and cottonseed in the form of meal) as protein sources for adult tilapia Oreochromis aureus x O. nilotica) was studied by using an inert marker in the feed and collecting the faeces by stripping. Each experimental diet consisted of 47.5 % different protein sources plus 52.5 % reference diet (50 % soybean meal, 35 % wheat flour, 10 % soybean oil, plus 5 % vitamins, egg yolk, guar and chromic oxide). It was found that the digestibility of protein in sunflower seed meal was 78 %, in rapeseed meal 86 % and in cottonseed meal 79 %. Digestible energy tests gave the following results: sunflower seed : 1712 cal/g; rapeseed : 2881 cal/g; cottonseed : 2225 cal/g. The difference in the digestibility of various protein sources is discussed